2009
DOI: 10.1088/0957-4484/21/1/015302
|View full text |Cite
|
Sign up to set email alerts
|

ZnTe–ZnO core–shell radial heterostructures grown by the combination of molecular beam epitaxy and atomic layer deposition

Abstract: ZnTe-ZnO core-shell radial heterostructures were grown using a new method of combining molecular beam epitaxy (MBE) and atomic layer deposition (ALD). Zinc telluride nanowires (core) were grown on a GaAs substrate using gold catalyzed vapor-liquid-solid mechanism. An atomic layer deposition technique using diethyl zinc and deionized water as precursors was applied for zinc oxide shell formation. The core-shell ZnTe-ZnO heterostructures thus obtained were characterized by scanning electron microscopy, transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Moreover, the conduction band (CB) of p-Cu 2 O is more negative than that of n-ZnO which favors the charge separation and transfer. More recently several works have focused on the synthesis and characterization of type-II core/shell arrays such as ZnO/ZnTe [16,17], ZnO/ZnSe [18][19][20] and ZnO/Cu 2 O [21][22][23]. In our case we are interested in Cu 2 O/ZnO core/shell nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the conduction band (CB) of p-Cu 2 O is more negative than that of n-ZnO which favors the charge separation and transfer. More recently several works have focused on the synthesis and characterization of type-II core/shell arrays such as ZnO/ZnTe [16,17], ZnO/ZnSe [18][19][20] and ZnO/Cu 2 O [21][22][23]. In our case we are interested in Cu 2 O/ZnO core/shell nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…It is transparent for visible and near infrared light even when heavily n-type doped. We demonstrated recently that the ZnO films grown by the ALD with free electron concentration at RT of 10 20 cm -3 [11,41,42] are suitable for the application as a transparent electrode in photovoltaic devices and in organic light emitting diodes (OLEDs). Moreover, we demonstrated that such films can replace ITO in practical devices.…”
Section: Zno For Optoelectronic and Photovoltaic Applications As Tranmentioning
confidence: 99%
“…One of the ways to improve NWs based devices is fabrication of nano-heterostructures such as radial structures consisting of a core and a shell built from two different materials providing function integration and novel applications [1][2][3][4]. Since ZnTe with its high band gap of 2.26 eV and easy p-type doping is a very attractive candidate for optoelectronic application it is very interesting to combine this material with other semiconductors, for example magnetic oxides.…”
Section: Introductionmentioning
confidence: 99%